A study of Korean femoral geometry - Khang, G; Choi, K; Kim, CS; Yang, JS; Bae, TS (LIPPINCOTT WILLIAMS & WILKINS, 2003)
The current authors investigated the anatomic geometry of femurs from Korean subjects and compared the results with those of femurs from American and Japanese subjects. Thirty-eight femurs extracted from cadavers and 200 femurs of healthy subjects were used. The 38 femurs were placed on a horizontal plane to obtain computed tomography images, which then were transformed into bitmap images, and the computed tomography images of the 200 femurs of healthy subjects also were obtained. Three-dimensional images of the femurs were reconstructed and used for measuring the parameters. The measurement results suggested that femurs from Korean subjects were different from femurs from American subjects. The major differences were that femurs from Korean subjects had a larger anteversion angle by approximately 8degrees, a relatively larger canal flare index, and there was a shorter distance between the lesser trochanter and the isthmus. These differences can provide useful information to the design of a new hip prosthesis for Korean, Japanese, and other Asian patients.
Keywords: ANTEVERSION